Hedge fund style investing : return persistence and information-ratio performance 1994-2004. - Huang, Alys Meiting. (2008)
Our applied research provides new evidence on the return persistence and the information-ratio performance of nine hedge fund strategies for the period from 1994 to 2004. The return persistence is measured by Hurst fractal exponent, whereas style portfolios’ performance is evaluated in terms of forward-looking information ratios.